2023
DOI: 10.3390/jcm12165165
|View full text |Cite
|
Sign up to set email alerts
|

Management of Spinal Metastasis by Minimally Invasive Surgical Techniques: Surgical Principles and Indications—A Literature Review

Mikael Meyer,
Kaissar Farah,
Toquart Aurélie
et al.

Abstract: Background: Spinal metastasis is becoming more frequent. This raises the topics of pain and neurological complications, which worsen the functional and survival prognosis of oncological population patients. Surgical treatment must be as complete as possible in order to decompress and stabilize without delaying the management of the oncological disease. Minimally invasive spine surgical techniques inflict less damage on the musculocutaneous plan than opened ones. Methods: Different minimally invasive techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Our findings aligned with those of previous studies that suggested minimally invasive spine surgery (MISS) offered significant advantages over traditional open procedures. For example, Meyer et al (2023) reported a substantial reduction in surgical site infections with MISS compared to open surgery in a large cohort of patients undergoing lumbar decompression and fusion [ 23 ]. Similarly, Conti et al (2019) emphasized the improved quality of life and reduced perioperative morbidity associated with MISS in patients with metastatic spinal cord compression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings aligned with those of previous studies that suggested minimally invasive spine surgery (MISS) offered significant advantages over traditional open procedures. For example, Meyer et al (2023) reported a substantial reduction in surgical site infections with MISS compared to open surgery in a large cohort of patients undergoing lumbar decompression and fusion [ 23 ]. Similarly, Conti et al (2019) emphasized the improved quality of life and reduced perioperative morbidity associated with MISS in patients with metastatic spinal cord compression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This statistical difference is given by a sub-classification in which thoracolumbar tumors were divided into thoracic, lumbar, and thoracolumbar, with the totality of these resulting in 40%, unlike previously reported literature. According to the literature, up to 30% corresponded to lesions in segments that were not contiguous at the time of metastasis diagnosis and may or may not be symptomatic [ 28 - 31 ]. Although we cannot define what caused this variability, it can be suspected that with a later diagnosis of a primary solid tumor, there is a greater probability that metastasis detected at the vertebral level will be present in two or more non-contiguous sites.…”
Section: Discussionmentioning
confidence: 99%